1,8-cineole, a TRPM8 agonist, is a novel natural antagonist of human TRPA1 - Takaishi Masayuki; Fujita Fumitaka; Uchida Kunitoshi; Yamamoto Satoshi; (Shimizu); (Uotsu); Shimizu Mayumi; Tominaga Makoto (SAGE Publishing, 2012)
Abstract Background Essential oils are often used in alternative medicine as analgesic and anti-inflammatory remedies. However, the specific compounds that confer the effects of essential oils and the molecular mechanisms are largely unknown. TRPM8 is a thermosensitive receptor that detects cool temperatures and menthol whereas TRPA1 is a sensor of noxious cold. Ideally, an effective analgesic compound would activate TRPM8 and inhibit TRPA1. Results We screened essential oils and fragrance chemicals showing a high ratio of human TRPM8-activating ability versus human TRPA1-activating ability using a Ca2+-imaging method, and identified 1,8-cineole in eucalyptus oil as particularly effective. Patch-clamp experiments confirmed that 1,8-cineole evoked inward currents in HEK293T cells expressing human TRPM8, but not human TRPA1. In addition, 1,8-cineole inhibited human TRPA1 currents activated by allyl isothiocyanate, menthol, fulfenamic acid or octanol in a dose-dependent manner. Furthermore, in vivo sensory irritation tests showed that 1,8-cineole conferred an analgesic effect on sensory irritation produced by TRPA1 agonists octanol and menthol. Surprisingly, 1,4-cineole, which is structurally similar and also present in eucalyptus oil, activated both human TRPM8 and human TRPA1. Conclusions 1,8-cineole is a rare natural antagonist of human TRPA1 that has analgesic and anti-inflammatory effects possibly due to its inhibition of TRPA1.